SOSIALISASI DAGUSIBU OBAT ANTIBOTIKA KEPADA MASYARAKAT PADA EVENT WORLD PHARMACIST DAY 2023 - Tuhfatul Ulya; Wulan Ratia Ratulangi (Politeknik Medica Farma Husada Mataram, 2023)
Health problems often occur because people do not know how to use and manage medicines properly, including antibiotics. Improper use of antibiotics can result in bacterial resistance. The use of antibiotics can be controlled by limiting antibiotic prescribing and educating the public. Providing education to the public can be done through socialization of DAGUSIBU - an antibiotic drug. This activity aims to educate the public regarding how to obtain, use, store and dispose of antibiotics correctly while at the same time familiarizing the community with a culture of healthy living. Activities were carried out at the 2023 World Pharmacist Day (WPD) event in collaboration with PD IAI NTB and the Indonesian Heart Foundation NTB. The socialization consisted of delivering material by a pharmacist, followed by a questions and answer session as well as a demonstration of DAGUSIBU - an antibiotic drug. The material was provided through DAGUSIBU antibiotic drug posters and also TB treatment leaflets, there was a quiz given at the end of the activity to see the participants' level of understanding. Socialization also includes using teaching aids for medicines with specific usage methods, as well as the correct way to dispose of tablets or syrup. The results of service activities show that the community understands how to obtain, use, store and dispose of antibiotic drugs properly and correctly.